Sequential extraction of RNA and DNA from the same sample of Neolamarckia cadamba (Roxb.) Bosser - Phui, Seng Loi; Ho Wei, Seng; Julaihi, Abdullah (2007)
Most of the established molecular techniques in plant molecular biology rely on the reliability of extraction methods to obtain nucleic acids from a given environmental source. The development of protocols for isolating both RNA and DNA from the same sample is recently becoming a major concern especially when the sample is small. Despite a number of methods that describe the simultaneous isolation of RNA and DNA from the same sample have been reported, most of these methods have yet to be optimized to deal with the reduced quantity and compromised quality of samples encountered in plant genetics analysis. Neolamarckia cadamba (Roxb.) Bosser was chosen in the present study due to its commercial value and fast growing ability. Total RNA was successfully isolated from the leaf tissue with subsequent recovery of DNA from the extraction mixture through alcohol precipitation. Reverse transcriptase‐Polymerase Chain Reaction (RT‐PCR) was performed and arbitrary primers that produced reproducible, scorable and informative bands were selected for randomly amplified polymorphic DNA (RAPD) analysis. The amplicons of RTPCR and RAPD were successfully obtained from all isolates, indicating that the extracted nucleic acids were intact and pure enough for quantitative molecular analysis.